A tonsillar location of a malignant schwannoma: a case report - Imane Boujguenna; Hind Ousehal; Atmane Zaroual; Mohamed E. L. Bouderkaoui; Abdelaziz Raji; Chihab Bouyaali; Najat Cherif Idrissi El Ganouni; Anass Fakhri; Hanane Rais (BMC, 2022)
Abstract Introduction Malignant schwannoma is a malignant tumor of differentiation of Schwann cells or perineural cells. Observation The patient was a 74-year-old woman with no particular pathological history. She presented swallowing difficulty of solids and odynophagia, evolving for 1 year. Physical examination revealed a budding tumor of the left palatine tonsil without cervical adenopathy. The CT scan confirmed the lesions and the absence of tumor extensions. Histological and immunohistochemical examination of the biopsy sample of the tonsil tumor concluded to be a malignant schwannoma. The patient underwent a tonsillectomy with postoperative follow-up. Discussion Malignant schwannomas are aggressive tumors. They usually occur in young adults. They mainly affect nerves and soft tissues. Occurrence in the amygdala is rare. Conclusion The association of malignant schwannoma of the palatine tonsil and advanced age is rare.